The Role of Digital Assessment in Developing Higher Order Thinking Skills (HOTS) in Students: A Systematic Literature Review - Eliaumra; Muhamad Aras; Shelvy Ferawati Rurua (Postgraduate, University of Mataram, 2026)
The aim of this study is to synthesise the strategic role of digital assessment in facilitating the development of Higher Order Thinking Skills (HOTS) in students through a Systematic Literature Review (SLR) approach. The main focus of this review encompasses the identification of characteristics of digital tools capable of stimulating the aspects of analysis, evaluation and creation. Key findings indicate that the effectiveness of HOTS development is highly dependent on the interface design and interactivity of the digital platform used, with real-time feedback and simulations of complex problem-solving emerging as key factors. The study’s conclusions affirm that systematically designed digital assessment can overcome the limitations of conventional evaluation in mapping students’ cognitive profiles in depth. The innovation offered by this study is a taxonomy of digital assessment relevant to the needs of the modern post-pandemic education curriculum. The results of this study are expected to serve as a reference for educational technology developers and practitioners in designing a more authentic, adaptive, and future-competency- oriented assessment ecosystem across various levels of education.